Effect of legume varieties and fermentation time of tempe using usar inoculum on the inhibitory activity of angiotensin I-converting enzyme - Retno Indrati; Marta T. Handayani; Novia Aristi Rahayu; Suci Apsari Pebrianti (Society for Indonesian Biodiversity, 2021)
Abstract. Indrati R, Handayani MT, Rahayu NA, Pebrianti SA. 2021. Effect of legume varieties and fermentation time of tempe using usar inoculum on the inhibitory activity of angiotensin I-converting enzyme. Biodiversitas 22: 5262-5267. The effect of three varieties of legumes, namely, velvet bean (Mucuna prurient), lima bean (Phasaelus lunatus L.), and pigeon pea (Cajanus cajan), on the activity of angiotensin I-converting enzyme (ACE) inhibitors was studied during tempe fermentation. Fermentation is one way to produce bioactive peptides. Furthermore, the effect of inoculum usar on tempe fermentation was studied. Hydrophobic amino acids are essential in binding firmly to the active site of ACE, and the research showed that pigeon pea had higher levels of hydrophobic amino acids compared with soybeans. The legumes affected the protease activity, peptide content, degree of hydrolysis, and production of ACE inhibitory (ACEI) activity during tempe fermentation. High protein levels and peptide content did not guarantee a high ACE inhibitor level. The mixed culture of usar caused no effect on the production of ACE inhibitors compared with a single culture of Raprima. Legume beans that reached optimal fermentation fast produced high levels of ACE inhibitors. Of the three types of legumes tested in the study, lima beans had the highest ACEI activity during fermentation.